A study to identify the risk factors associated with infertility among women attending infertility clinics - B., Ramanath; Kumar G., Amar; Subrahmanyam, Venkata B.; Kumari K., Sandhya (International Journal of Research in Medical Sciences, 2025)
Background: Infertility is not a newly emerging issue; it has its crux from the olden days. It is a preexisting problem and a threat to the social integration of families. The impact of this problem contributes a lot to the disharmony among young couples. Methods: Present study is a quantitative approach and descriptive design. It consists of the demographic variables, gynecological factors, psychological factors, lifestyle factors, physical measures, diagnosed cause of infertility and hormonal values. Results: A total of 400 women participated in the study, in that 100 cases randomly selected. It was observed that women with infertility (76%) were within the age group of 21-30 years of age, (85%) of them had a primary education and (89%) of them were home makers (77%) them were living in a nuclear family, Hindus (77%) and also reside at urban region (52%). Experience marital conflicts (70%) It was inferred that a higher proportion of women (93%) are non-vegetarians, more than half them (63%) have a meal pattern of 2 meals, Conclusions: The study concluded that irregular menstrual cycle, marital and familial conflicts, overweight, more of non-vegetarian foods, lack of exercise etc. were some common risk factors associated with infertility. The study thus also had a conclusion that with certain awareness on the modifiable factors and ways to modify them will always contribute towards betterment of women’s health in terms of fertility.